Effect of Plant Growth Regulators on Growth and Quality Flower Production of Chrysanthemum (Chrysanthemum Indicum L.) - Md Ehsanullah; Ahasan Ullah Khan; Md Kamruzzam; Sarah Tasnim (Journal of Multidisciplinary Applied Natural Science, 2022)
A field study was conceded to assess the effect of plant growth regulators on growth and quality flower production of chrysanthemum at Horticulture Research Centre (HRC), Gazipur, Bangladesh. The experiment was laid out in Randomized Complete Block Design (RCBD) with ten (10) treatments and three replications. The treatments of plant growth regulators concentration were T1-50 ppm GA3, T2-100 ppm GA3, T3-150 ppm GA3, T4-400 ppm CCC, T5-600 ppm CCC, T6-800 ppm CCC, T7-250 ppm MH, T8-500 ppm MH, T9-750 ppm MH and, T10-Control. The maximum spreading of plant (27.0 cm) was observed when plants were treated with GA3 @ 150 ppm where the minimum plant spread (16.8 cm) was recorded in plants treated with CCC @ 800 ppm. The higher number of suckers (33) per pot was produced when pots were treated with GA3 @ 150 ppm whereas, application of CCC at three different concentrations produced lower number of suckers.  The highest number of flower (40) was recorded with 150 ppm GA3, where minimum number of flowers (25) per pot in 800 ppm CCC. The plants sprayed with 50 ppm GA3 took 48 days to flower initiation, whereas, it took 70 days with 750 ppm MH. the highest plants recorded (7.40 cm) with 800 ppm CCC, whereas, lowest size (6.50 cm) was obtained with the application of 500 ppm MH. The maximum vase life of flowers was recorded for the treatment 800 ppm CCC (15 days), which was at par with 13 days vase life obtained by spraying 600 ppm CCC. Therefore, it is concluded that the GA3 acted as growth promoter and the CCC acted as growth retardants on yield and quality of chrysanthemum.